Chronic mesenteric ischaemia masked by candida esophagitis in a renal transplant patient. Issue 12 (30th December 2019) - Scheetz, Seth; Pandey, Deepali; Pesavento, Todd E; Singh, Priyamvada
Abstract : Chronic mesenteric ischaemia is a severe disease that is often missed due to its non-specific presentation. Immunosuppressed patients are at risk for infectious gastrointestinal disease, which may further obscure the diagnosis of chronic mesenteric ischaemia. In this case, a patient's symptoms and diagnostic workup were consistent with candida esophagitis. Worsening leukocytosis despite treatment, however, prompted re-evaluation ultimately revealing a superior mesenteric artery thrombus causing mesenteric ischaemia. The patient required urgent surgical intervention for the management of his disease.